Alport syndrome caused by a COL4A5 deletion and exonization of an adjacent AluY. Issue 5 (28th May 2014) - Nozu, Kandai; Iijima, Kazumoto; Ohtsuka, Yasufumi; Fu, Xue Jun; Kaito, Hiroshi; Nakanishi, Koichi; Vorechovsky, Igor
Abstract Mutation‐induced activation of splice sites in intronic repetitive sequences has contributed significantly to the evolution of exon–intron structure and genetic disease. Such events have been associated with mutations within transposable elements, most frequently in mutation hot‐spots of Alus. Here, we report a case of Alu exonization resulting from a 367‐nt genomic COL4A5 deletion that did not encompass any recognizable transposed element, leading to the Alport syndrome. The deletion brought to proximity the 5′ splice site of COL4A5 exon 33 and a cryptic 3′ splice site in an antisense AluY copy in intron 32. The fusion exon was depleted of purines and purine‐rich splicing enhancers, but had low levels of intramolecular secondary structure, was flanked by short introns and had strong 5′ and Alu‐derived 3′ splice sites, apparently compensating poor composition and context of the new exon. This case demonstrates that Alu splice sites can be activated by outlying deletions, highlighting Alu versatility in shaping the exon–intron organization and expanding the spectrum of mutational mechanisms that introduce repetitive sequences in mRNAs.